Underwear : fashion in detail - Lynn, Eleri (New York, NY : Abrams, 2010)
Ranging from camisoles to corsets, basques to boudoir caps and girdles to garters, this title deals with some of the most intimate items in the V&A. It traces the evolution of underwear. It features photography that shows close-up details of these garments. It also highlights the work of designers such as Vionnet and Westwood.
boek